Peningkatan Pengetahuan Siswa tentang Pemanfaatan dan Pengolahan Toga: Formulasi Nuigum (Nutraceticals Immune Booster Gummy Candy) - Budiyanto, Ratno; Hasanah, Ulfatun; Purnama, Prasasti Mia (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2025)
The utilization and processing of Family Medicinal Plants (TOGA) is part of the solution to overcome health problems. Among the family medicinal plants, turmeric and Javanese ginger have benefits as immunomodulators. The purpose of this activity is to Increase Student Knowledge About the Utilization and Processing of TOGA: Formulation of NUIGUM (Nutraceticals Immune Booster Gummy Candy) Turmeric Extract (Curcuma longa) and Javanese Ginger (Curcuma xanthorriza) as an Immune Booster with Variations of Adding Siwalan Sugar (Borassus flabellifer l). The method used is socialization and education on the importance of the benefits and processing of TOGA to students of grades X and XI Pharmacy as an indicator of Asta Cita science, technology and health. The results of this activity show an increase in the percentage of student knowledge from 10% to 85%. This community service is expected to open new business opportunities for students while supporting the achievement of Sustainable Development Goals (SDGs), namely a healthy and prosperous life.